Nelson Mandela : a very short introduction - Boehmer, Elleke (Very short introductions, 2008)
As well as being a remarkable statesman, Nelson Mandela has become a universal symbol of justice, a secular saint. Elleke Boehmer examines not only the great anti-apartheid leader's life, but also the ways in which images and representations have been used to create the Mandela we know today - an internationally recognized icon of freedom. - ;As well as being a remarkable statesman and one of the world's longest-detained political prisoners, Nelson Mandela has become an exemplary figure of non-racialism and democracy, a moral giant. Once a man with an unknown face, he became after his 1994 release one of the most internationally recognizable images of our time. Set within a biographical frame, this Very Short Introduction explores the reasons why his story is so important to us in the world at large today, and what his achievements signify. It shows how our picture of Mandela is a great deal more complicated than the legend suggests: quality of character is combined with his talents as a performer, his maverick ability to absorb transnational influences, his proximity to outstanding colleagues, his steely survival skills, and his. postmodern ease with media image. It shows how many different interconnected stories, histories, values, and symbols combine in the famous name Nelson Mandela . - ;An excellent overview of his career...[and] much more than just a "Very Short Introduction". - Independent.